BIMBINGAN KELOMPOK BERBASIS DARING TERHADAP PENINGKATAN PENYESUAIAN SISWA SMA KELAS X - Rahayu Tresnasari; Euis Eti Rohaeti; Alvian Agung Nurhaqy (IKIP Siliwangi, 2023)
Self-adjustment of high school students is a process / effort carried out by individuals in dealing with new environments, new friends, new teachers with the aim of being accepted by others as in the previous school environment (SMP). This Online Implementation is a service process carried out by BK teachers to their students who have problems related to adjustment during the COVID-19 pandemic. As a result, all students are required to participate in all online learning activities (on the network). The purpose of holding this service is so that students can solve problems and get solutions related to self-adjustment assisted by BK teachers, and other students, one of which is by discussing, asking questions, via Whatsapp Group, researcher uses instruments in form interviews, observations and documentation. The results of this study students feel helped and can adapt well, so that the service process held at SMAN 1 Cipongkor can be carried out smoothly.Keywords: Self-Adjustment, Group Guidance, Online